Analisis Hukum Terhadap Pertanggungjawaban Pelaku Pidana Penggelapan (Studi Kasus Pada Pengadilan Negeri Lubuk Pakam) - Manik, Bisker; Mulyadi, Mahmud; Zul, Muaz (ARBITER: Jurnal Ilmiah Magister Hukum, 2019)
This study aims to look criminologically and juridically about crime in human actions that compromises the basic norms of society. Actions of elements that break the rules that live and develop in society. This type of research is analytical descriptive of juridical normative, the main material in this research is secondary data which is done by collecting material in the form of: Primary Legal Material, namely legal material in the form of laws and regulations, official documents that have authority related to the problem , namely the Criminal Code. Secondary Legal Material, which is all legal material which is an unofficial document publication including books, scientific works. Tertiary Legal Materials, i.e. materials that provide and explain primary and secondary legal materials, such as public dictionaries, legal dictionaries, scientific journals, magazines, newspapers and the internet that are still relevant to this research, research results and discussions to explain the elements the element of embezzlement consists of elements of subjective offense in the form of a deliberate offender to embezzle the assets of others as defined in the article of the law through the words: intentionally and the element of Oyective violation consists of: anyone's element, element of illegally controlling, object elements, elements partially or wholly owned by others and the object elements there are not for crime.